Traffic planning in port-cities - Peter Hall (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
Port container trucking is currently one of the most challenging aspects of the love-hate relationship between ports and cities. This paper highlights important examples of emerging good practices at and around the marine port terminal. Hinterland connectivity and landside productivity are increasingly important for port performance. Yet conflicts over congestion, pollution and other negative impacts of container traffic are an increasing source of tensions. Managing these tensions requires a clear understanding of the issues and identification of the stakeholders involved in the transport system of the immediate port hinterland.
Keywords: 330